KONSTRUKSI GENDER MELALUI ORNAMEN HIAS PADA SENJATA TRADISIONAL KHAS SUMBAWA BARAT - Rahmat, Mi'rajus Subyan; Muhammad Tomi; Bayu Aji Pamungkas (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research deals with how the construction of gender is realized through decorative ornaments carved on berang traditional weapons in the community of Rempe Village, Seteluk District, West Sumbawa Regency. Berang is a traditional weapon of the Samawa tribe (Sumbawa) in the form of a cutting weapon made by a panre (blacksmith). In general, the people of Sumbawa recognize two types of berang namely the salaki berang (male), and the swai berang (female). The use of the term berang as a relative (brother), as well as the differences in the ornamentation of the two types of berang, is the reason for this research. The problem of this research is dissected by using Roland Barthes' semiotic concept. The results of this study indicate that in general, gender construction does occur through berang. This gender construction produces